Pengembangan Modul Pembelajaran Matematika Berbasis Etnomatematika Menggunakan Metode Inkuiri - Mardiah, Siti; widyastuti, Rany; Rinaldi, Achi (Universitas Islam Negeri Raden Intan Lampung, 2018)
This research entitled Development of Mathematics Based Module of Ethnomathematics using Inkuiri method. This study aims to find out how the development of mathematics learning module based on ethnomathematics using inquiry method, and to know the teacher and student response to the development of mathematics learning module based on ethnomathematics using inquiry method. This research method is Research and Development (R&D) using 4D model. Based on the results of the validation of stage 1 by the material experts obtained a cumulative average of 65.36% with the criteria of